Roland Barthes’ Semiotics on Political Posters For the Election of Regent and Vice Regent of Malang In 2024 - Rachma, Rula Nadia (International Journal on Advanced Science, Education, and Religion, 2025)
This research aims to analyze the types of signs, symbols, words and colors from semiotics and describe the denotation, connotation, mythical and cultural meanings of each sign and symbol contained in political posters for the 2024 Malang Regency Regent and Deputy Regent elections. Observation was conducted using descriptive qualitative to observe the meaning based on Barthes'(1977) semiotic theory, this analysis includes the identification of denotation meaning (literal meaning), connotation (additional meaning), and myth (hidden meaning) of each sign and word. Coding was given to each sign to facilitate analysis and categorization. Thematic analysis was conducted to identify the main themes and political messages conveyed. The results of the analysis are presented in the form of narratives and images to clarify the meaning and political messages contained in the posters. The results of this study found 10 datum consisting of signs, symbols, colors and words, each of which is seen from the meaning of denotation, connotation and myth. It was found that the revealed meaning provides teasers or clues and invitations for the community as voters. Keyword: Semiotics, Political posters, Barthes' semiotic theory